Removal of Formaldehyde Using Highly Active Pt/TiO2 Catalysts without Irradiation - Haibao Huang; Huiling Huang; Peng Hu; Xinguo Ye; Dennis Y. C. Leung (International Journal of Photoenergy)
Formaldehyde (HCHO) is one of the major indoor air pollutants. TiO2 supported Pt catalysts were prepared by sol-gel method and used to eliminate HCHO at room temperature without irradiation. The reduced Pt/TiO2 catalyst (denoted as Pt/TiO2-H2) showed much higher activity than that calcined in air (denoted as Pt/TiO2-air). More than 96% of the conversion of HCHO was obtained over 0.5 wt% Pt/TiO2-H2, on which highly dispersed metallic Pt nanoparticles with very small size (~2 nm) were identified. Metallic Pt rather than cationic Pt nanoparticles provide the active sites for HCHO oxidation. Negatively charged metallic Pt nanoparticles facilitate the transfer of charge and oxygen species and the activation of oxygen.